Agrárnagyüzemek működési nehézségei a Dráva mentén 1920 körül - Kaposi, Zoltán (Közép-Európai Közlemények, 2023)
This paper examines the changes that took place in the functioning of estates on either side of the Drava river, a region dominated by large estates, towards the end of the World War I and the following years. Our research covered 21 estates from both the Hungarian and Slavonian sides of the Drava. The analysis shows that the years under discussion were quite eventful in this region. Three main effects are highlighted in the paper. One is the occupation then annextion of the manors on he right bank of the Drava in the western part of the region into the Kingdom of Yugoslavia. The second is land reform and „socialisation” in early 1919 affecting the remaining estates within the new borders. The third is the serbian occupation: between 13 November 1918 and 21 August 1921 the area to he south of the Barcs - Szigetvár - Baja line, that is the larger part of the Drava valley, was under serbian occupation, which was then systematically robbed. These effects significantly restricted the functioning of the Drava valley estates. Apart from this, further difficulties arose with the Treaty of Trianon (loss of the Muraköz and Drávaszög districts): the land reform associated with Nagyatádi, the property redemption act, the loss of former markets etc. all had a long-term impact on the workings of the agrarian large estates.